2005
DOI: 10.1364/ol.30.002354
|View full text |Cite
|
Sign up to set email alerts
|

Correlated two-photon imaging with true thermal light

Abstract: We report the first experimental demonstration of two-photon correlated imaging with true thermal light from a hollow cathode lamp. The coherence time of the source is much shorter than that of previous experiments using random scattered light from a laser. A two-pinhole mask was used as object, and the corresponding thin lens equation was well satisfied. Since thermal light sources are easier to obtain and measure than entangled light it is conceivable that they may be used in special imaging applications.Alt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
204
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 366 publications
(207 citation statements)
references
References 16 publications
2
204
1
Order By: Relevance
“…This result re ects the relation between the value of the autocorrelation function and the number of modes, already shown in Eqs. (7) and (9). In more detail, we notice that since the CCD camera is a macroscopic detector, the two expressions of g ( ) simplify as the last term on the right side can be neglected.…”
Section: Experimental Results: Application To Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…This result re ects the relation between the value of the autocorrelation function and the number of modes, already shown in Eqs. (7) and (9). In more detail, we notice that since the CCD camera is a macroscopic detector, the two expressions of g ( ) simplify as the last term on the right side can be neglected.…”
Section: Experimental Results: Application To Imagingmentioning
confidence: 99%
“…The image of the object is recovered by correlating the intensities measured by the bucket detector with the intensities measured by each pixel of the spatial-resolving detector [3]. The geometry of light propagation required to reconstruct the image depends on the speci c kind of correlated beams in use: ghost imaging protocols with twin beams require the use of lenses [4][5][6][7], while those performed with thermal light can be lensless [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The first experiment was demonstrated with entangled light obtained from spontaneous parametric down conversion, 1 and the phenomenon was once considered as a characteristic of the nonlocality of entanglement, 2 hence the name "ghost" imaging was coined. Later, it was found that thermal light can also be used to realize GI, [3][4][5][6][7][8][9][10][11] which has many advantages as the source is readily available and has higher intensity so less data acquisition time is needed. However, a fundamental disadvantage is that there is always a large background, which restricts the maximum visibility to 1/3, compared to 1 for entangled light.…”
Section: Author(s) All Article Content Except Where Otherwise Notedmentioning
confidence: 99%
“…The results were similar to those with the entangled source, but with half the visibility. It has since been shown that spatial correlations present in radiation produced using thermal and speckle sources may also lead to ghost imaging ( [4][5][6][7][8][9]). …”
Section: Two-photon Ghost Imagingmentioning
confidence: 99%